Anticholinergic burden in older inpatients on psychotropic medication: do we care?. (December 2017) - Lee, Mei Shiang; Kisely, Steve; Zolotarev, Boris; Warren, Andrew; Henderson, Jack; George, Manoj
Objectives: This quality activity explored the prescribing patterns in an Older Persons Mental Health Inpatient Unit in order to establish whether the Anticholinergic Cognitive Burden Scale (ACB Scale) score on admission was reviewed to minimise anticholinergic cognitive burden (ACB) while maintaining therapeutic effects. Methods: A retrospective electronic chart review of 50 discharged patients for any documented ACB review by the treating team, as well as the ACB Scale scores on admission and discharge. Findings: ACB was rarely considered. On average, the total ACB Scale scores on admission and discharge were high. At the time of discharge, the proportion of patients on at least one anticholinergic medication had significantly increased, and only 10% of patients were on no anticholinergic medication. Approximately 50% of patients had an increased ACB Scale score by discharge as opposed to only 8% who had reduced scores. Conclusions: Anticholinergic polypharmacy should be minimised when prescribing to the elderly population to reduce potential anticholinergic burden.